Combination of treatments to improve thermal stability of egg albumen. (October 2016) - Kulchaiyawat, Charlwit; Wang, Chao; Yu, Chenxu; Han, Zhaopeng; Wang, Tong
Abstract: Protein modification with combined pre-heating, sonication, and the addition of octenyl succinic anhydride (OSA) was performed on egg albumen to improve its thermal stability. The treatments applied to fresh egg white (FEW, or albumen) led to an increased stability. The pre-heating step and high level of OSA addition, such as 20% relative to protein, were beneficial when the stability of protein was evaluated at a higher temperature of 95 °C or 121 °C compared to that of 75 °C. The low level of OSA treatment, such as 5%, showed improved thermal stability evaluated by turbidity and protein solubility at 75 °C. Thus, the optimal level of OSA addition would depend on the degree of thermal stability improvement needed. The use of Raman spectroscopy method revealed that there were strong interactions between OSA and albumen protein and that this complex was more resistant to structural changes by heating. A mechanistic explanation of thermal stabilization based on experimental observations was illustrated. This is the first study that utilizes OSA along with other physical means to complex and stabilize egg proteins. Highlights: A combination of treatments improved thermal stability of egg albumen. OSA is a unique molecule with dual functions that can interact and stabilize proteins. Several methods of thermal stability evaluation were used that showed different sensitivities. The ability of Raman spectroscopy to detect structural changes is discussed. The mechanism of thermal stabilization of OSA-albumen complex is proposed.